Into rather unexplored terrain—transcellular transport across the blood–brain barrier. Issue 7 (8th February 2016) - De Bock, Marijke; Van Haver, Valérie; Vandenbroucke, Roosmarijn E.; Decrock, Elke; Wang, Nan; Leybaert, Luc
Abstract : Efficient neuronal signaling in the central nervous system strictly depends on a well‐balanced microenvironment around glial cells, synapses, and axons. Unique features of the blood–brain barrier (BBB) endothelium largely determine the composition of this micro‐milieu and are dependent on the tight interplay with surrounding astrocytes and pericytes. BBB endothelial cells are endowed with a highly restrictive junctional complex that occludes the intercellular cleft, thereby preventing paracellular diffusion. The paracellular pathway is subject to extensive research as integrity loss of the junctional complex is associated with many neuropathologies, inflammation, and edema. Another important feature of the BBB endothelium is the low prevalence of nonspecific, transcytotic events, including (macro)pinocytosis, clathrin‐dependent and caveolin‐dependent endocytosis and the subsequent trafficking of vesicles to the opposite membrane. Although less studied, evidence is accruing that this pathway importantly contributes to increased BBB permeability, often when the junctional complex remains intact. Here, we review current knowledge on the contribution of the transcellular pathway to the BBB leak observed in different pathologic conditions. In addition, we hypothesize that nonselective, large pore connexin and pannexin channels may contribute to transcellular transport, either by providing a direct diffusion pathway across the endothelial monolayer, or indirectly, by exerting control over intracellular levels of the signaling ion Ca 2+ that is involved in many steps of the vesicular pathway. We conclude that transcytotic events at the BBB, despite being less acknowledged, cannot be simply dismissed as done in the past, but actively contribute to BBB leakage in many different pathologies. GLIA 2016;64:1097–1123 Main Points: In addition to paracellular leakage, transcytosis involving endo/exocytosis and large pore channels contributes to BBB dysfunction in various neuropathologies. Control of transcytosis thus provides unexplored possibilities to modulate BBB function.